Norwegian Equivalents to Lithuanian Rhemic Secondary Parts of the Sentence - Griškevičienė, Aurelija (Kalbotyra, 2009)
The theme-rheme (topic-focus) structure of a sentence is inherent in all the languages of the world. The difference lies in the means of functional sentence perspective, which is determined by the grammatical structure of a language. It is especially obvious in languages of different typology (e.g. synthetic and analythic). The aim of this article is to investigate expressions of Norwegian equivalents to Lithuanian remic secondary parts of the sentence (object and adverbial modifier) in the Lithuanian language. The analysis resorts for illustrations to the short story “Gyvenimas po klevu” by Granauskas and its translation into Norwegian.The analysis shows, the secondary parts of the sentence can be made rhemic in the Norwegian language by the following means: various syntactic constructions (cleft, the reduplication of a sentence part), replacing one sentence part with other sentence part of the same meaning, alterations in the expression of the sentence part, syntactic order reshuffling, inversion, the passive voice, introduction of extra elements.Both languages display the principle of the end position of the rheme, in both languages the object and the adverbial modifier can be rhemised by way of inversion. In the case the rhemic object or the rhemic adverbial modifier occupies the last position in a sentence in the Norwegian language, some extra means of focus of the object and the adverbial modifier are needed.
Keywords: theme; rheme; Lithuanian; Norwegian; translation